Effectiveness of video education on intention for cervical cancer screening - Nanik Setiyawati; Niken Meilani; Nur Khafidhoh (Intelektual Pustaka Media Utama, 2022)
Cervical cancer represents 7.5% of deaths caused by cancer in women. Prevention of cervical cancer can be done by cervical cancer screening. The purpose of the study was to determine the effect of video on knowledge level, attitude, and intention for cervical cancer screening in Yogyakarta. This study was a quantitative study with a quasi-experimental nonequivalent control group design. The study was carried out in April-October 2021. The population of the study was all women of childbearing age. The sample was 50 respondents for each group, experiment group and control group. The intervention was given through video education for the experiment group and pocketbooks for the control group. Data analysis used T-test, Wilcoxon test, and Mann-withney. There was a difference in the pre-test and post-test of knowledge level (p=0.002), attitude (p=0.023), intention (p=0.005) in the experiment group and knowledge level (p=0.001), attitude (p=0.000), intention (p=0.004) in the control group. There was a significant difference in women’s intention (p=0.001) for cervical cancer screening with the video education method than pocketbooks. The method of providing educational videos and pocketbooks is effective for increasing the knowledge level, attitude, and intention for cervical cancer screening. Video has influence on intention to detection cervical cancer.